2014
DOI: 10.1186/1476-511x-13-32
|View full text |Cite
|
Sign up to set email alerts
|

Absence of clinical relationship between oxidized low density lipoproteins and diabetic peripheral neuropathy: a case control study

Abstract: BackgroundThe pathophysiology of diabetic peripheral neuropathy (DPN) is complex and uncertain. A potential comorbidity in diabetes mellitus (DM) that may contribute to greater severity of DPN is a lipid disorder, such as with elevated cholesterol, low density lipoproteins or triglycerides. Oxidized low density lipoprotein (oxLDL) is a form of cholesterol that exerts direct toxic effects and contributes to pathogenicity through ligating a receptor called lectin-like receptor (LOX-1).MethodsWe examined plasma o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…In addition, OxLDL correlate with symptom severity in patients with fibromyalgia (20,21). However, oxidized LDL levels remain comparable in patients with and without polyneuropathy due to type 2 diabetes (22). Notably, OxPL levels also rise in many other diseases (13).…”
Section: Oxidized Phospholipids Are Linked To Inflammatory Conditions and Painmentioning
confidence: 99%
“…In addition, OxLDL correlate with symptom severity in patients with fibromyalgia (20,21). However, oxidized LDL levels remain comparable in patients with and without polyneuropathy due to type 2 diabetes (22). Notably, OxPL levels also rise in many other diseases (13).…”
Section: Oxidized Phospholipids Are Linked To Inflammatory Conditions and Painmentioning
confidence: 99%
“…Finally, 38 studies were selected to find a relationship between LDL and SBP levels and risk of diabetic peripheral neuropathy [417, 22, 33–55]. Of the 38 finalized studies, 2 studies [22, 55] and 7 studies [6, 10, 1416, 35, 47, 50, 52] were excluded involving insufficient data to find a relationship between LDL and SBP levels and risk of DPN, respectively. Hence, in this current meta-analysis, only 29 articles were attempts to find a relationship between SBP levels and DPN in type 2 diabetes mellitus patients.…”
Section: Resultsmentioning
confidence: 99%
“…)LDL (mmol/L)SBP (mmHg) P -value*N (M/F)Age (yrs. )LDL (mmol/L)SBP (mmHg) P -value**Zhao W. et al [4]365 (230/135)59.482.75 ± 0.86130.29 ± 15.930.01104 (53/51)66.942.62 ± 0.82135.81 ± 17.650.133Wu F. et al [5]560 (338/222)53.202.84 ± 0.96129.10 ± 17.30<0.01574 (307/267)61.002.66 ± 0.95134.4 ± 18.400.002ALMA R. et al [6]12 (6/6)53.602.20 ± 0.70NANA70 (46/24)60.232.30 ± 1.25NANAYang J. et al [7]1287 (626/661)58.612.78 ± 1.01132.06 ± 20.540.03224 (117/107)66.582.75 ± 0.99134.72 ± 22.250.438Bilir B. et al [8]53 (24/29)58.853.59 ± 1.40128.97 ± 11.73NA46 (23/23)56.913.15 ± 0.99131.62 ± 14.25NASharon L. et al [9]1767 (866/901)57.202.76 ± 0.83137.60 ± 18.70< 0.01214 (135/79)60.102.71 ± 0.81146.00 ± 20.600.45Yong J. et al [10]90 (50/40)54.902.90 ± 0.88NANA90 (46/44)54.102.73 ± 0.82NA0.18Su J. et al [11]461 (248/213)56.002.67 ± 0.82134.00 ± 17.000.10102 (51/51)58.402.60 ± 0.86137.00 ± 19.000.44Zhang Y. et al [12]642 (342/300)60.032.92 ± 0.96134.29 ± 19.140.00417 (247/170)61.662.95 ± 1.15142.50 ± 22.390.60Won J. et al [13]2661 (1346/1315)59.402...…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that low levels of HDL increased the risk of diabetic peripheral neuropathy [ 13 ]. Rosales-Hernandez et al after examining oxidized LDL (OxLDL) in diabetic peripheral neuropathy concluded that there was no association between its level and occurring peripheral neuropathy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%